2001
DOI: 10.4141/p00-116
|View full text |Cite
|
Sign up to set email alerts
|

Potential of controlling insect pests of corn using entomopathogenic nematodes

Abstract: Riga, E., Whistlecraft, J. and Potter, J. 2001. Potential of controlling insect pests of corn using entomopathogenic nematodes. Can. J. Plant. Sci. 81: 783-787. A series of experiments was performed in the laboratory and in the greenhouse to assess the efficacy of the entomopathogenic nematodes, Steinernema glaseri or S. feltiae in decreasing the numbers of European corn borer, fall armyworm, western corn rootworm and the seedcorn maggot in corn. Both nematode species effectively controlled the four insect pes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 17 publications
4
18
0
Order By: Relevance
“…These results are similar to those observed by Riga et al (2001). Testing the efficiency of the S. glaseri and S. The concentration of Heterorhabditis sp.…”
Section: Susceptibility Of D Speciosa Larvae To Entomopathogenic Nemsupporting
confidence: 80%
“…These results are similar to those observed by Riga et al (2001). Testing the efficiency of the S. glaseri and S. The concentration of Heterorhabditis sp.…”
Section: Susceptibility Of D Speciosa Larvae To Entomopathogenic Nemsupporting
confidence: 80%
“…the nematode and fungus, may be influenced by soil-related (Jackson 1995) or application-related factors (Brust 1991;Ellsbury et al 1996;Susurluk 2005). This may be the reason that several authors reported inconsistent results when using such biological agents Wright et al 1993;Jackson and Brooks 1995;Riga et al 2001). These factors may also be the reason that both the fungus and the nematode failed once in field 1 of this study.…”
Section: Discussionmentioning
confidence: 54%
“…Some studies show high efficacies, while others show low efficacies (e.g. for fungi: Krueger and Roberts 1997;for nematodes: Georgis and Gaugler 1991;Wright et al 1993;Jackson and Brooks 1995;Riga et al 2001; for soil insecticides and seed coatings: Zhu et al 2005;Borani et al 2006;Furlan et al 2006;Parimi et al 2006;Van Rozen and Ester 2007). Occasional failures of fungi or nematodes are usually explained by the use of species or strains that are not adapted to the host or to local conditions (Jackson 1995;Shapiro-Ilan et al 2002), by soil aridity and soil texture (Ellsbury et al 1996;Kessler et al 2003;Koppenhöfer and Fuzy 2006) or by the lack of alternative hosts (Brust 1991;Susurluk 2005).…”
mentioning
confidence: 97%
“…Field studies employing the entomopathogen species used in the current study have shown decreased survival of rootworm in a number of cases (Krueger and Roberts 1997;Journey and Ostlie 2000;Toepfer et al 2008Toepfer et al , 2010Pilz et al 2009). However, entomopathogen efÞcacy, particularly with nematodes, has also been shown to be variable and sometimes inconsistent under Þeld conditions, and can depend on many factors including environmental conditions, application method, concentration, and strain (e.g., Wright et al 1993, Jackson and Brooks 1995, Riga et al 2001.…”
Section: Discussionmentioning
confidence: 99%